Hydrodynamics and stability of Group B Streptococcus polysaccharides and CRM197 protein - MacCalman, Thomas (2023)
Group B Streptococcus is a pathogen that chiefly infects immunocompromised individuals and neonates. To combat this infection, at-risk mothers are currently given antibiotics before birth to prevent exposure of neonates to the bacteria. A vaccine would be beneficial, as it would allow mothers to combat this infection without excessive use of antibiotics. As encapsulated bacteria, the main structure available as a target antigen is the polysaccharide capsule itself, rather than any underlying structures. For this reason, glycoconjugate vaccines are being synthesised which use surface polysaccharides conjugated to carrier proteins to improve their immunogenicity. This project studies the stability of candidate polysaccharides for use in a glycoconjugate vaccine. The polysaccharides were provided by GSK vaccines, who requested the use of specific hydrodynamic methodology. The polysaccharides were found to be generally stable, only seeing small changes in hydrodynamic properties after exposure to stress, but in many cases it is likely that the differences seen are due to minor experimental variation rather than genuine structural differences. The polysaccharides were also tested for possible association effects with blood plasma proteins: serum albumin, fibrinogen and immunoglobulin. The polysaccharides were again found to be stable in the presence of these molecules.